1998
DOI: 10.1080/109158198226756
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of Monochloro-1,2-Propanediol (α-Chlorohydrin, 3-MCPD)

Abstract: B a r ry S . L y n ch , D ou g la s W . B ry a n t , G ra h a m J . H ook , E a r le R . N est m a n n , a n d I a n C . M u n ro C a n Tox, I n c, M is s is s a u g a , O n t a r io, C a n a d a -M on och l or o-1 ,2 -p r op a n ed i ol (-M C P D ) i s a b y -p r od u ct f ou n d i n t r a ce a m ou n t s , gen er a l ly l es s t h a n 1 m g/ k g (<1 p p m ), in h y d rol yz ed v eget a b l e p r ot ein p r od u ced t h rou gh a cid h y d r ol y si s. I n a ch r on ic s t u d y w it h F 4 4 r a t s , h igh d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
21

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 58 publications
2
69
0
21
Order By: Relevance
“…3-MCPD has also been detected in various heat-processed foods, including cereal-derived products like bread crust, toast and biscuits, malt-derived products, coffee, and grilled cheese, as well as smoke-treated products (Bakhiya et al, 2011;Schallschmidt et al, 2012;Teng and Wang, 2014). The toxicity of 3-MCPD is well-documented and includes neurotoxicity (Cavanagh and Nolan, 1993), nephrotoxicity (Velisek et al, 1980), genotoxicity (Lynch et al, 1998), immunotoxicity (Lee et al, 2004) and reproductive toxicity (Lynch et al, 1998). Recently, 3-MCPD was classified by the IARC as group 2B, "possibly carcinogenic to humans" (Bakhiya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…3-MCPD has also been detected in various heat-processed foods, including cereal-derived products like bread crust, toast and biscuits, malt-derived products, coffee, and grilled cheese, as well as smoke-treated products (Bakhiya et al, 2011;Schallschmidt et al, 2012;Teng and Wang, 2014). The toxicity of 3-MCPD is well-documented and includes neurotoxicity (Cavanagh and Nolan, 1993), nephrotoxicity (Velisek et al, 1980), genotoxicity (Lynch et al, 1998), immunotoxicity (Lee et al, 2004) and reproductive toxicity (Lynch et al, 1998). Recently, 3-MCPD was classified by the IARC as group 2B, "possibly carcinogenic to humans" (Bakhiya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is an increasing awareness that CPN can be a risk factor for the spontaneous development of renal tubule tumors in rats (Figure 4), particularly in the male (Lipsky and Trump, 1988;Hard, 1998). Furthermore, evidence is emerging that certain chemicals can interact with CPN to increase the incidence of CPN-related proliferative lesions (Hard et al, 1997;Lynch et al, 1998;Hard, 2002). This association appears to be restricted to the most advanced stages of the disease process.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the toxicological, metabolic and mechanistic data on 3-MCPD (LYNCH et al 1998) showed its genotoxicity in vitro, but there was no evidence of genotoxicity in vivo. It was concluded that tumours reported in certain animals had de-veloped as a result of non-genotoxic mechanisms and were considered not to be relevant to humans exposed to trace amounts of 3-MCPD.…”
mentioning
confidence: 99%